Strategi Kepala Madrasah Dalam Optimalisasi Sarana Prasarana di Madrasah Aliyah - Nurwinda Aulia Nasution; Syafri Fadillah Marpaung (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2023)
Optimization strategies are very important to support learning activities in limited facilities. the purpose of this study was to determine how the strategy of the head of the madrasah in the optimization of infrastructure experienced obstacles and solutions by the head of the madrasah, as well as how the results of the implementation of the strategy of the head of the madrasah in the optimization of infrastructure. This study uses descriptive qualitative research methods. The results showed that the strategy for optimizing infrastructure in MAS Muhammadiyah 1 Medan involves management activities that include planning, organizing, implementing, and evaluating. The constraints experienced are generally in the form of limited funds and locations that are not wide enough so the solution that can be done is to procure the facilities and make optimal use of the available infrastructure. The success of the madrasah head's strategy in optimizing infrastructure can be seen from the procurement, utilization, and good inventory and increasing the creativity and innovation of teachers and students in utilizing available facilities.